A 2,4,5-trifluorophenylacetic acid-modified α-Fe2O3-based perovskite solar cell and a preparation method thereof

By modifying the α-Fe2O3 electron transport layer with 2,4,5-trifluorophenacetic acid, the problems of low energy conversion efficiency and poor stability of α-Fe2O3-based perovskite solar cells are solved, and the energy conversion efficiency and ultraviolet stability are improved.

CN115000306BActive Publication Date: 2025-03-18HAINAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210658227.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-10
Publication Date
2025-03-18
Estimated Expiration
2042-06-10

AI Technical Summary

Technical Problem

Due to the surface defects of α-Fe2O3, short charge diffusion length and insufficient electron extraction capacity of α-Fe2O3, the energy conversion efficiency and poor stability.

Method used

2,4,5-trifluorophenacetic acid is used to modify the α-Fe2O3 electron transport layer, passivate the hydroxyl defect on the surface of α-Fe2O3 and coordinate with the Pb2+ ions in the perovskite layer, promote charge extraction and reduce non-radiative recombination at the interface.

Benefits of technology

The energy conversion efficiency of perovskite solar cells was significantly improved, from 16.27% to 18.08%, and the stability of the cell was significantly improved under ultraviolet irradiation conditions, with the energy conversion efficiency dropping by only 5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115000306B_ABST
    Figure CN115000306B_ABST
Patent Text Reader

Abstract

The invention discloses an α-Fe2O3-based perovskite solar cell modified by 2,4,5-trifluorophenylacetic acid, comprising a transparent conductive substrate layer and an electron transport layer, a passivation layer, a perovskite photosensitive layer, a hole transport layer and a metal electrode which are sequentially stacked on the transparent conductive substrate layer, wherein the electron transport layer is an α-Fe2O3 film, the passivation layer is 2,4,5-trifluorophenylacetic acid, the perovskite photosensitive layer is a hexavalent mixed perovskite film, and the hole transport layer is a 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene layer. That is, the present invention uses a solution method to prepare a 2,4,5-trifluorophenylacetic acid interface layer film and uses it to simultaneously passivate the α-Fe2O3 electron transport layer and the perovskite photosensitive layer of the perovskite photovoltaic cell. The method is simple and easy to mass produce. It can not only passivate the inherent defects on the surface of the α-Fe2O3 electron transport layer, but also enhance the interface charge transfer and inhibit interface recombination, thereby significantly improving the energy conversion efficiency and ultraviolet stability of the α-Fe2O3 perovskite solar cell of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic device preparation, and in particular to an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite materials have attracted widespread attention due to their excellent optoelectronic properties, low cost, and solution processability. In recent years, perovskite solar cells (PSCs) based on organic-inorganic hybrid perovskite light-absorbing materials have developed rapidly, and the power conversion efficiency (PCE) has soared from 3.8% to 25.7%. In the development and evolution of perovskite solar cells, the electron transfer layer (ETL) plays a vital role in charge extraction, electron transfer, and hole blocking, and has an important impact on the separation and recombination of photogenerated charges. So far, titanium dioxide and tin dioxide are still the most commonly used electron transport materials, achieving record performance in perovskite solar cells. However, perovskite solar cells using TiO2 ETL show rapid performance decay under strong ultraviolet irradiation. This is due to the presence of many oxygen vacancies (or Ti 3+ These oxygen vacancies will adsorb oxygen molecules from the air to form a charge transfer complex O2-Ti 4+ . However, this oxygen adsorption is unstable. Under ultraviolet light excitation, the holes on the TiO2 valence band recombine with the electrons on the oxygen adsorption point, causing the adsorbed oxygen molecules to be released, forming a free electron and a positively charged oxygen vacancy on the conduction band. The free electron quickly recombine with the surplus holes on the hole transport material. The defect state energy level caused by the remaining oxygen vacancies is about 1eV below the bottom of the conduction band. The photogenerated electrons will transfer to these deep trap energy levels through the vibration energy levels of the molecules. These electrons cannot jump to the conduction band of the electron transport layer again, and can only recombine with the holes inside the battery or be localized in these defects, resulting in a significant decrease in battery performance.

[0003] Studies have shown that α-Fe2O3 is a potential electron transport material that can replace traditional TiO2 in planar heterojunction perovskite solar cells. Compared with traditional TiO2 ETL, α-Fe2O3 has better hole blocking ability and higher UV stability. However, α-Fe2O3 itself has inherent defects such as surface hydroxyl groups and poor energy level matching with the perovskite light absorption layer, resulting in a short charge diffusion length and insufficient electron extraction ability. Therefore, planar perovskite solar cells based on α-Fe2O3 still have low energy conversion efficiency, and the general energy conversion efficiency is about 16% at most, which is difficult to further optimize and improve.

[0004] Therefore, it is urgent to develop a preparation method for perovskite solar cells that passivate the α-Fe2O3 electron transport layer / photosensitive layer interface with 2,4,5-trifluorophenylacetic acid, which is of great significance for improving the energy conversion efficiency of α-Fe2O3-based perovskite solar cells. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid, which solves the problems of low energy conversion efficiency and poor stability of α-Fe2O3 planar perovskite solar cells due to surface defects of α-Fe2O3 itself, short charge diffusion length and insufficient electron extraction ability.

[0006] On one hand, the present invention provides a perovskite solar cell in which an α-Fe2O3 electron transport layer / photosensitive layer interface is passivated with 2,4,5-trifluorophenylacetic acid. The solar cell comprises a transparent conductive substrate layer and an electron transport layer, a passivation layer, a perovskite photosensitive layer, a hole transport layer and a metal electrode which are sequentially stacked on the transparent conductive substrate layer. The transparent conductive substrate is FTO conductive glass, the electron transport layer is an α-Fe2O3 film, the passivation layer is 2,4,5-trifluorophenylacetic acid, the perovskite photosensitive layer is a hexavalent mixed perovskite film, and the hole transport layer is a 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene layer.

[0007] On the other hand, a method for preparing an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid is provided, comprising the following steps:

[0008] (1) cleaning and drying the transparent conductive substrate layer;

[0009] (2) treating the pretreated transparent conductive substrate layer with ultraviolet ozone for standby use, then spin-coating the transparent conductive substrate layer with an α-Fe2O3 precursor solution, and then sintering to obtain an α-Fe2O3 electron transport layer;

[0010] (3) spin coating 60 μL of a 2,4,5-trifluorophenylacetic acid solution with a concentration of 0.2-0.5 mg / mL on the α-Fe2O3 electron transport layer film to prepare a 2,4,5-trifluorophenylacetic acid passivation layer;

[0011] (4) spin coating a perovskite precursor solution on the 2,4,5-trifluorophenylacetic acid passivation layer, and before the spin coating is completed, an anti-solvent is titrated on the perovskite film to prepare a perovskite photosensitive layer;

[0012] (5) spin coating a hole transport layer precursor solution on the surface of the perovskite photoactive layer to prepare a hole transport layer;

[0013] (6) A gold electrode is evaporated on the surface of the hole transport layer to obtain a planar structure perovskite photovoltaic cell.

[0014] Preferably, in step (2), the concentration of the α-Fe2O3 precursor solution is 0.08 mg / mL, the dosage is 65 μL, and the thickness of the α-Fe2O3 electron transport layer is 40 nm.

[0015] Preferably, in step (3), the concentration of the 2,4,5-trifluorophenylacetic acid solution is 0.35 mg / mL.

[0016] Preferably, in step (4), the perovskite precursor solution is obtained by dissolving 190 mg FAI, 21.8 mg MABr, 548 mg PbI2, and 77 mg PbBr2 in 1 mL of a mixed solvent of DMF and DMSO in a volume ratio of 4:1 and 34 μL of CsI solution and stirring for 12 hours; the titration amount of the perovskite precursor solution is 65 μL; and the anti-solvent is chlorobenzene.

[0017] Preferably, in step (5), the hole transport layer precursor solution is prepared by mixing 1 mL of a chlorobenzene solution containing 72.3 mg of Spiro-OMeTAD, 29 μL of 4-tert-butylpyridine and 17.5 μL of a 520 mg / mL lithium bis(trifluoromethanesulfonyl)imide solution.

[0018] Preferably, in step (6), a gold electrode is prepared on the surface of the hole transport layer by a vacuum evaporation process, and the thickness of the gold electrode is 80 nm.

[0019] In summary, the present invention provides a method for preparing an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid, which uses the special group structure in 2,4,5-trifluorophenylacetic acid to passivate the hydroxyl groups on the surface of the α-Fe2O3 electron transport layer and compound with uncoordinated metal ions; at the same time, the oxygen in the C=O bond in 2,4,5-trifluorophenylacetic acid can provide a lone electron pair as a Lewis base to react with the uncoordinated Pb in the perovskite layer. 2+ coordination, thereby promoting the extraction of charges, reducing the non-radiative recombination at the interface, and improving the photovoltaic performance of the device.

[0020] On the other hand, the perovskite solar cell prepared by the present invention not only has an energy conversion efficiency increased from 16.27% to 18.08%, a significant increase of 10%; -2) irradiation, and found that the energy conversion efficiency of the battery that had not been passivated with 2,4,5-trifluorophenylacetic acid decreased by 21% after 240 hours of irradiation, and was only 79% of the initial value; while the energy conversion efficiency of the α-Fe2O3 perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid only decreased by 5%, and the stability performance of the battery was also significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a device structure diagram of an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid.

[0022] Figure 2 It is the ultraviolet transmission spectrum of the surface of α-Fe2O3-based perovskite solar cell, wherein A is the ultraviolet transmission spectrum of the surface of the α-Fe2O3 electron transport layer of comparative example 1 which is not modified by 2,4,5-trifluorophenylacetic acid; B is the ultraviolet transmission spectrum of the surface of the α-Fe2O3 electron transport layer modified by 2,4,5-trifluorophenylacetic acid in example 1.

[0023] Figure 3 1 is a current density and voltage (JV) curve of a perovskite solar cell, wherein curve A represents a perovskite solar cell of comparative example 1 that is not modified with 2,4,5-trifluorophenylacetic acid; and curve B represents a perovskite solar cell of example 1 that is modified with 2,4,5-trifluorophenylacetic acid.

[0024] Figure 4 For perovskite solar cells in the ultraviolet (365nm, 5mW cm -2 ) were used to perform a UV stability test under ambient conditions, wherein curve A represents the comparative example 1 perovskite solar cell that was not modified with 2,4,5-trifluorophenylacetic acid; and curve B represents the example 1 perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid. DETAILED DESCRIPTION

[0025] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0026] Embodiment 1: Figure 1 A method for preparing an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid comprises the following steps:

[0027] (1) Pretreatment of transparent conductive substrate: To clean the FTO (fluorine-doped SnO2) conductive glass sheet, first place the conductive glass sheet in a solution containing a detergent and ultrasonicate it for 15 minutes, then repeatedly wash it with deionized water until the foam is washed away; then place it in containers containing acetone and alcohol and ultrasonicate it for 25 minutes respectively; finally, store it in anhydrous ethanol and blow it dry with a nitrogen gun when using it.

[0028] (2) Preparation of α-Fe2O3 film: The cleaned FTO conductive glass was placed in a UV-ozone cleaning instrument for 20 minutes. 32.32 mg of ferric nitrate nonahydrate was completely dissolved in 1 mL of anhydrous ethanol. Ultrasonic treatment was performed for 10 minutes to obtain a 0.08 mg / mL α-Fe2O3 precursor solution. 65 μL of the α-Fe2O3 precursor solution was spin-coated on the conductive glass using a sizing machine. The spin-coating speed was 4000 rpm and the spin-coating time was 40 seconds. The glass was then placed in a muffle furnace and sintered at 500°C for 60 minutes. The heating rate was 5°C / min. After cooling in the furnace, a 40 nm thick α-Fe2O3 electron transport layer was obtained.

[0029] (3) Preparation of 2,4,5-trifluorophenylacetic acid passivation layer on α-Fe2O3 film:

[0030] a. Dissolve 0.35 mg of 2,4,5-trifluorophenylacetic acid powder in 1 mL of anhydrous ethanol and stir on a magnetic stirrer for 2 h before use;

[0031] b. Use a coating machine to spin coat 60 μL of 2,4,5-trifluorophenylacetic acid solution (concentration of 0.35 mg / mL) on the α-Fe2O3 film at a spin coating rate of 4000 rpm for 30 s. Anneal at 100°C for 30 min to form a 2,4,5-trifluorophenylacetic acid passivation layer film.

[0032] (4) Preparation of perovskite photosensitive layer:

[0033] a. Perovskite (Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 ))3 Preparation of precursor solution: 190 mg FAI, 21.8 mg MABr, 548 mg PbI2, and 77 mg PbBr2 were mixed and dissolved in 1 mL of a mixed solvent of DMF and DMSO (volume ratio of 4:1), 34 μL of CsI solution was added, and the mixture was mixed and stirred for 12 h under an inert gas atmosphere for standby use;

[0034] b.(Cs 0.05 MA 0.16 FA 0.79 Pb(I0.83 Br 0.17 3. Preparation of thin film: In an inert gas box, 65 μL of the prepared perovskite precursor solution was spin-coated at a rate of 4500 rpm for 45 s on the passivation layer (Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 ))3 film, and 13s before the end of spin coating, drop 200μL of chlorobenzene on the (Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 ))3 film surface, and then annealed at 110℃ for 60min to finally obtain (Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 ))3 Photoactive layer.

[0035] (5) Preparation of Spiro-OMeTAD hole transport layer: 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene solution, and 29 μL of 4-tert-butylpyridine tBP and 17.5 μL of lithium bis(trifluoromethanesulfonyl)imide solution Li-TFSI (concentration of 520 mg / mL, solvent: acetonitrile) were added thereto. The hole transport layer precursor solution was obtained by ultrasonication for 6 min. 60 μL of the precursor solution was spin-coated at a speed of 4000 rpm for 20 s on the photosensitive layer (Cs 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 ))3 Prepare the Spiro-OMeTAD hole transport layer on the film.

[0036] (6) Preparation of electrodes: A gold electrode with a thickness of about 80 nm was obtained on the surface of Spiro-OMeTAD by vacuum evaporation to obtain a planar structure perovskite photovoltaic cell.

[0037] Example 2: The difference between Example 2 and Example 1 is that in step (3), a 2,4,5-trifluorophenylacetic acid passivation layer is prepared on the α-Fe2O3 film:

[0038] a. Dissolve 0.5 mg of 2,4,5-trifluorophenylacetic acid powder in 1 mL of anhydrous ethanol and stir on a magnetic stirrer for 2 h before use;

[0039] b. Use a coating machine to spin coat 60 μL of 2,4,5-trifluorophenylacetic acid solution (concentration of 0.5 mg / mL) on the α-Fe2O3 film at a spin coating rate of 4000 rpm for 30 s. Anneal at 100°C for 30 min to form a thin film.

[0040] Embodiment 3: The difference between Embodiment 3 and Embodiment 1 is that:

[0041] In step (3), a 2,4,5-trifluorophenylacetic acid passivation layer is prepared on the α-Fe2O3 film:

[0042] a. Dissolve 0.2 mg of 2,4,5-trifluorophenylacetic acid powder in 1 mL of anhydrous ethanol and stir on a magnetic stirrer for 2 h before use;

[0043] b. Use a coating machine to spin coat 60 μL of 2,4,5-trifluorophenylacetic acid solution (concentration of 0.2 mg / mL) on the α-Fe2O3 film at a spin coating rate of 4000 rpm for 30 s. Anneal at 100°C for 30 min to form a thin film.

[0044] Comparative Examples 1 to 3: The difference from Example 1 is that Comparative Examples 1 to 3 do not include a 2,4,5-trifluorophenylacetic acid passivation layer, and in step (2), 65 μL of α-Fe2O3 precursor solutions of different concentrations are used for spin coating to prepare the α-Fe2O3 electron transport layer.

[0045] The performance of the α-Fe2O3-based perovskite solar cells prepared in Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:

[0046] Table 1: Performance comparison of α-Fe2O3-based perovskite solar cells prepared from α-Fe2O3 precursor solutions with different concentrations (without passivation layer modification)

[0047]

[0048] It can be seen from Table 1 above that without the modification of the passivation layer, the energy conversion efficiency of the solar cell prepared in Comparative Example 1 is 14.85% to 16.27%, and when the volume of the spin-coated α-Fe2O3 precursor solution is 65 μL and the concentration is 0.08 mg / mL, that is, when the thickness of the electron transport layer is 40 nm, the energy conversion efficiency of the solar cell is as high as 16.27%.

[0049] The perovskite solar cells prepared in Examples 1 to 3 and Comparative Example 2 were characterized and tested for performance. The results are shown in Table 2 below.

[0050] Table 2 Performance comparison of perovskite solar cells of Examples 1 to 3 and Comparative Example 2

[0051]

[0052] Depend on Figure 2 The results show that the ultraviolet transmittance of the surface of the α-Fe2O3-based perovskite film modified with 2,4,5-trifluorophenylacetic acid does not change much, indicating that the spin-coated 2,4,5-trifluorophenylacetic acid passivation layer has little effect on the structure of the α-Fe2O3-based perovskite thin film battery of the present invention; Figure 3-4 As shown in Table 2, the energy conversion efficiency of the perovskite solar cell of the present invention increases sharply from 16.27% to 18.08%. -2 ) irradiation, and found that after 240h irradiation, the energy conversion efficiency of the battery in comparative example 2 decreased by 21%, which was only 79% of the initial value; while the energy conversion efficiency of the perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid only decreased by 5%, and the stability of the battery was significantly improved.

[0053] In summary, the present invention provides a method for preparing an α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid, wherein a 2,4,5-trifluorophenylacetic acid passivation layer is prepared on an α-Fe2O3 electron transport layer by a spin coating method, and the preparation method is simple and easy to mass produce; and 2,4,5-trifluorophenylacetic acid can simultaneously passivate the inherent defects on the surface of the α-Fe2O3 electron transport layer and the defects on the interface of the buried layer, thereby reducing charge recombination at the interface, thereby significantly improving the photovoltaic performance and ultraviolet stability of the prepared device, and providing a feasible solution for accelerating the industrialization of perovskite solar cells in the future.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An α-Fe2O3-based perovskite solar cell modified with 2,4,5-trifluorophenylacetic acid, characterized in that: The invention comprises a transparent conductive substrate layer and an electron transport layer, a passivation layer, a perovskite photosensitive layer, a hole transport layer and a metal electrode which are sequentially stacked on the transparent conductive substrate layer, wherein the electron transport layer is an α-Fe2O3 film, the passivation layer is 2,4,5-trifluorophenylacetic acid, the perovskite photosensitive layer is a hexavalent mixed perovskite film, and the hole transport layer is a 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene layer.

2. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 1, characterized in that: The following steps are involved: (1) cleaning and drying the transparent conductive substrate layer; (2) treating the pretreated transparent conductive substrate layer with ultraviolet ozone for standby use, then spin-coating the transparent conductive substrate layer with an α-Fe2O3 precursor solution, and then sintering to obtain an α-Fe2O3 electron transport layer; (3) spin coating 60 μL of 0.2-0.5 mg / mL 2,4,5-trifluorophenylacetic acid solution on the α-Fe2O3 electron transport layer film to prepare a 2,4,5-trifluorophenylacetic acid passivation layer; (4) spin coating a perovskite precursor solution on the 2,4,5-trifluorophenylacetic acid passivation layer, and before the spin coating is completed, an anti-solvent is titrated on the perovskite film to prepare a perovskite photosensitive layer; (5) spin coating a hole transport layer precursor solution on the surface of the perovskite photoactive layer to prepare a hole transport layer; (6) A gold electrode is evaporated on the surface of the hole transport layer to obtain a planar structure perovskite photovoltaic cell.

3. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 2, characterized in that: The concentration of the α-Fe2O3 precursor solution is 0.08 mg / mL, the dosage is 65 μL, and the thickness of the α-Fe2O3 electron transport layer is 40 nm.

4. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 2, characterized in that: In the step (3), the concentration of the 2,4,5-trifluorophenylacetic acid solution is 0.35 mg / mL.

5. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 2, characterized in that: In the step (4), the perovskite precursor solution is prepared by dissolving 190 mg FAI, 21.8 mg MABr, 548 mg PbI2, and 77 mg PbBr2 in 1 mL of a mixed solvent of DMF and DMSO in a volume ratio of 4:1 and 34 μL of CsI solution, and stirring for 12 hours; the titration amount of the perovskite precursor solution is 65 μL; and the anti-solvent is chlorobenzene.

6. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 2, characterized in that: In the step (5), the hole transport layer precursor solution is prepared by mixing 1 mL of a chlorobenzene solution containing 72.3 mg of Spiro-OMeTAD, 29 μL of 4-tert-butylpyridine, and 17.5 μL of a 520 mg / mL lithium bistrifluoromethanesulfonimide solution.

7. The method for preparing a 2,4,5-trifluorophenylacetic acid modified α-Fe2O3-based perovskite solar cell according to claim 2, characterized in that: In the step (6), a gold electrode is prepared on the surface of the hole transport layer by using a vacuum evaporation process, and the thickness of the gold electrode is 80 nm.

Citation Information

Patent Citations

  • Method for preparing high-efficiency carbon electrode inorganic perovskite solar cell from phenylalkylamine derivatives

    CN111540808A